Analysis of the Performance Quality of the Information System and Information Technology of the Shopee Application Using Cobit 2019 - Kevin Fransisco; Hendry (INOVTEK Polbeng - Seri Informatika, 2025)
This research analyzes the quality of information system and information technology performance in the Shopee application using the COBIT 2019 framework. This research uses quantitative methods by collecting Likert scale-based questionnaire data, which was distributed to 112 respondents from Satya Wacana Christian University students class of 2020-2023. The technical analysis includes validity tests, reliability tests, t-tests, and ANOVA, with the |aim of determining the rel| relationship between gender |and cl|ass v|ari|ables on user s|atisf|action. The rese|arch results show th|at aspects of responsiveness and empathy h|ave |a signific|ant influence on user s|atisf|action, with a value of t = 1.685 (men) and t = 1.698 (women), as well as a p-value > 0.05 which shows there is no signific|ant difference based on gender. The 2019 COBIT Evaluation shows weaknesses in IT risk management, and optimization of IT resources, as well as the need to improve data security and customer service systems, and optimization of IT infrastructure. This research contributes to understanding the application of COBIT 2019 in IT govern|ance in e-commerce and provides recommendations for improvements for Shopee in improving user experience. The limit|ation of this research is | that the s| sample is limited to one institution and a certain period, so the results cannot be widely generalized.